PERAN ELITE LOKAL DALAM PEMEKARAN DESA (STUDI KASUS DESA PINDI WANGGA WUNDUT, KECAMATAN LEWA, KABUPATEN SUMBA TIMUR) - Hamariu, Frengki; Noak, Piers Andreas; Erawan, I Ketut Putra (Jurnal Nawala Politika, 2020)
ABSTRACT        A study of the role of local elites in the process of separating the village of Pindi Wangga Wundut, Lewa District, East Sumba Regency. research method used is descriptive quali tatives . Using the theories of Vilfredo Pareto and Gaetano Mosca as references in research. Research shows that the role of local elites cannot be separated from the effects of change in the political system. The elite, which is the main driving force for the formation  autonomous regions, often makes village expansion an arena of struggle and power struggles. The formation of an autonomous region can create a new power space. Therefore, the local elite of the Pindi Wangga Wundut village will try to take a position to secure power. In conclusion, this did not happen in the Pindi Wangga Wundut village, because the expansion of the village was purely the desire of the community without interference from other parties. Keywords: Expansion, Elite, Community ABSTRACT        A study of the role of local elites in the process of separating the village of Pindi Wangga Wundut, Lewa District, East Sumba Regency. research method used is descriptive quali tatives . Using the theories of Vilfredo Pareto and Gaetano Mosca as references in research. Research shows that the role of local elites cannot be separated from the effects of change in the political system. The elite, which is the main driving force for the formation  autonomous regions, often makes village expansion an arena of struggle and power struggles. The formation of an autonomous region can create a new power space. Therefore, the local elite of the Pindi Wangga Wundut village will try to take a position to secure power. In conclusion, this did not happen in the Pindi Wangga Wundut village, because the expansion of the village was purely the desire of the community without interference from other parties. Keywords: Expansion, Elite, Community